CUP-syndrome: Inguinal high grade serous ovarian carcinoma lymph node metastases with unknown primary origin – a case report and literature review - Restaino, Stefano; Mauro, Jessica; Zermano, Silvia; Pellecchia, Giulia; Mariuzzi, Laura; Orsaria, Maria; Titone, Francesca; Biasioli, Anna; Della Martina, Monica; Andreetta, Claudia; Poletto, Elena; Arcieri, Martina; et al. (Frontiers in Oncology, 2022)
Objective: High-grade serous ovarian carcinoma often presents lymph node involvement. According to the ways of lymphatic drainage, the most common site of metastasis is para-aortic and caval, but frequently pelvic lymph nodes are also involved. Metastases to the inguinal lymph nodes are less frequent. Methods: We report the case of a 78-year-old woman with inguinal lymph node recurrence of high-grade serous ovarian carcinoma, with a previous history of positive right inguinal lymph node at the first diagnosis and negative ovaries and tubes on histological examination. A comprehensive search of the literature published from January 2000 to October 2021was conducted on PubMed and Scopus. Papers selection was performed following the PRISMA guidelines. Nine retrospective studies were selected. Results: A total of 67 studies were included in the initial search. Applying the screening criteria, 36 articles were considered eligible for full-text reading, of which, after applying the exclusion criteria, 9 studies were selected for the final analysis and included in the systematic review. No studies were included for a quantitative analysis. We divided the results according to the location of the recurrence: locoregional recurrence, abdominal recurrence and extra abdominal recurrence. Conclusions: Inguinal lymph nodes metastasis is a rare condition, but not infrequent. A reasonable level of suspicion should be maintained in patients with inguinal lymphadenomegalies and high CA125 value, especially if they have a history of previous gynecologic surgery, even if imaging is negative for ovarian disease.